2009
DOI: 10.1016/j.drugalcdep.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Interim methadone treatment: Impact on arrests

Abstract: AIMS This study examines the frequency and severity of arrest charges among heroin addicts randomly assigned to either interim methadone maintenance (IM) or to remain on a waiting list for methadone treatment. It was hypothesized that IM participants would have a: 1) lower number of arrests at 6 and 12 months and 2) lower mean crime severity scores at 6 and 12 months post-baseline. METHODS Available official arrest data were obtained for all 319 study participants for a period of 2 years before and after stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 28 publications
2
46
1
Order By: Relevance
“…In a clinical trial with 319 newly-admitted methadone patients, the group randomly assigned to receive methadone treatment without counseling (termed interim maintenance) for 4 months followed by entry into standard methadone treatment was compared to the group assigned to a waiting list control and encouraged to call the local methadone programs for admission. The interim methadone group had a significantly greater reduction in the number of arrests at 6-months post-study enrollment compared with the waiting list control group (Schwartz et al, 2009). In that study participants who were on probation or parole at baseline did as well as, or better than, participants not on probation or parole in terms of illicit drug use and criminal activity at 12-month follow-up (Kelly, O’Grady, Jaffe, Gandhi, Schwartz, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…In a clinical trial with 319 newly-admitted methadone patients, the group randomly assigned to receive methadone treatment without counseling (termed interim maintenance) for 4 months followed by entry into standard methadone treatment was compared to the group assigned to a waiting list control and encouraged to call the local methadone programs for admission. The interim methadone group had a significantly greater reduction in the number of arrests at 6-months post-study enrollment compared with the waiting list control group (Schwartz et al, 2009). In that study participants who were on probation or parole at baseline did as well as, or better than, participants not on probation or parole in terms of illicit drug use and criminal activity at 12-month follow-up (Kelly, O’Grady, Jaffe, Gandhi, Schwartz, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, while approval of buprenorphine (Suboxone ® ) extended maintenance treatment into general medical practices, many areas of the country have an insufficient number of willing providers, due to physicians’ concerns about induction logistics, reimbursement challenges, potential for medication diversion, lack of support for providers and lack of psychosocial services for patients (Barry et al, 2009; Becker & Fiellin, 2006; Kissin et al, 2006; Netherland et al, 2009; Sigmon, in press). The result is that many opioid-dependent individuals needing treatment can remain on waitlists for weeks or months, particularly those who must await admission to a subsidized program (Schwartz et al, 2009, 2011; Sherba et al, 2012). During this delay to treatment, they are at significant risk for continued illicit drug use, criminal activity, infectious disease, overdose and mortality (Adamson & Sellman, 1998; Clausen et al, 2009; Cooper, 1989; Darke & Hall, 2003; Schwartz et al, 2009; Warner-Smith et al, 2001; Wenger & Rosenbaum, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…17,18,20 In addition, HIV risk, and arrest appear to be reduced. 2122 Interim methadone can be scaled up relatively quickly to treat large numbers of patients in numerous programs and at a low cost (estimated at a few dollars per week/patient added to an existing program) that could be subsidized by low payments from the patients themselves. 23 Extant data from three clinical trials with methadone 37,53,54 indicate that early in treatment, patients receiving methadone alone fare as well as those who receive methadone with counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the interim group compared to those on the waiting list were found, over the course of two follow-up interviews at 4- and 10-months post-study entry, to have an increased likelihood of entering and remaining in standard methadone treatment and of reducing: opioid use 20 ; HIV risk behavior 21 ; criminal behavior 20 ; and, arrest. 22 This randomized trial suggested that interim methadone was an effective approach that suggested greater public health benefits and reductions in criminal activity when waiting lists were a significant barrier to treatment entry…”
Section: Introductionmentioning
confidence: 99%